Anxiety and Diminished Hope: The Potential Impact of Trump's Presidency on Security in the Pacific Islands Region. Issue 2 (4th March 2017) - Ratuva, Steven
Abstract: The election of Donald Trump as the next president of the US has caused much international consternation and anxiety. Reactions have been based on distrust and rejection of Trump's political ideology, behavioural disposition and unpredictable policy positions. His campaign speeches were filled with provocative utterances which were racist, sexist, homophobic, anti-environment and self-centred. This article examines some possible impacts of Trump's presidency on the Pacific island countries (PICs). The first issue refers to how Trump's proposed isolationist and militarisation policies may affect regional geopolitics. The two policies tend to contradict each other because while isolationism means pulling back on US economic and strategic presence in the Pacific, a reversal of the pivot to Asia-Pacific policy, militarisation implies greater strategic reach, regionally and globally. What does this seemingly contradictory approach mean for the PICs? Second, the article looks at the impact of Trump's climate change denial stance and the responses by PICs, given the fact that climate change is the single most significant foreign policy and development initiative of the PICs since their independence. The third issue deals with the potential impact of Trump's restrictive migration policies on remittance flow to the PICs and how these affect the small island economies and well-being.